2014
DOI: 10.1371/journal.pone.0090987
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Egg Washing and Correlation between Eggshell Characteristics and Egg Penetration by Various Salmonella Typhimurium Strains

Abstract: Salmonella is an important foodborne pathogen, causing an estimated 11,992 cases of infection in Australia per year. Egg or egg product related salmonellosis is a major concern for the egg industry. Worldwide, S. Typhimurium is one of the most common serovars identified in Salmonella food poisoning cases. The current study investigated the ability of five S. Typhimurium strains to penetrate washed and unwashed eggs using whole egg and agar egg penetration methods. All S. Typhimurium strains were able to penetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(45 citation statements)
references
References 23 publications
1
41
0
3
Order By: Relevance
“…These findings are in agreement with our previous survey (6), in which all egg internal contents were Salmonella negative. The egg penetration experiment indicated that S. Worthington has a capacity to penetrate the eggshell but lacks the ability to survive in the egg internal contents (V. C. Gole, unpublished data), whereas S. Typhimurium has a capacity to penetrate and survive in egg internal contents at 20°C (26). In the present experiment, even though chickens were positive for S. Typhimurium, the egg internal contents were Salmonella negative.…”
Section: Discussionmentioning
confidence: 42%
“…These findings are in agreement with our previous survey (6), in which all egg internal contents were Salmonella negative. The egg penetration experiment indicated that S. Worthington has a capacity to penetrate the eggshell but lacks the ability to survive in the egg internal contents (V. C. Gole, unpublished data), whereas S. Typhimurium has a capacity to penetrate and survive in egg internal contents at 20°C (26). In the present experiment, even though chickens were positive for S. Typhimurium, the egg internal contents were Salmonella negative.…”
Section: Discussionmentioning
confidence: 42%
“…Fresh grade A shell eggs were purchased from a local grocery store (West Lafayette, IN). Four fresh shell whole eggs (grade A) were soaked in 70% (v/v) ethanol for 30 min at room temperature and air‐dried in a sterile hood to prevent sample contamination before they were broken . Shells were broken using a sterile spoon and placed in the sterile blender.…”
Section: Methodsmentioning
confidence: 99%
“…The survival of S. Typhimurium PT 135, an egg product related outbreak strain, was assessed on eggshells and the results indicated the persistence of this strain on the egg shell up to four weeks (McAuley et al 2015). Previous findings from the authors' laboratory showed that S. Typhimurium strains were able to survive on an eggshell for up to 21 days (Gole et al 2014c). While the formation of biofilm was not assessed in either study, this could be one of the likely mechanisms that bacteria use to persist on eggshell.…”
Section: Discussionmentioning
confidence: 96%